Trade regimes as a tool for cyber policy. Issue 1 (14th January 2019) - Grindal, Karl
Abstract : Purpose: This research develops a framework for assessing international trade regimes which could be used to address global cybersecurity challenges based on the corresponding costs of implementation and their distribution. Trade regimes, such as export controls, tariffs, investment restrictions and localization requirements, have disparate effects on foreign and domestic producers and consumers. Design/methodology/approach: These trade regimes and their effects are explored through a literature review and conceptual framework. A case study then assesses trends in the use of the Committee on Foreign Investment in the United States (CFIUS). Findings: CFIUS investment restrictions have justified blocking specific Chinese acquisitions of American companies, at least partially, on cybersecurity grounds using a targeted and evidence-based approach. Because of its targeted effect, CFIUS is the least likely of these trade regimes to block legitimate international trade. Restrictions on international trade, without sufficient cause, produce dead weight loss under the theory of comparative advantage. Originality/value: These costs should be accounted for in any policy-based decision, particularly as policy entrepreneurs increasingly push for embedding cybersecurity reforms into these trade regimes. While the literature on trade regimes and cybersecurity is growing, this paper advances this research with its comparative framework.